Avaliação da exposição da população as aflatoxinas pelo consumo de amendoim em Maringá, Brasil - Santos, Aline Cristini dos (2015)
Peanut is a food widely consumed worldwide, due to its nutritional properties and its accessibility. In Brazil, due to tropical and subtropical characteristics of the country, peanut samples often are contaminated by fungi produce toxins, mainly the species: Aspergillus flavus and Aspergillus parasiticus, aflatoxin producers.Aflatoxins are hepatocarcinogenics, particularly aflatoxin B1. Human exposure aflatoxins is through consumption of contaminated food. This study aimed to to evaluate the exposure of the population aflatoxins in peanuts marketed in the city of Maringa, Parana State, Brazil, during the period from May 2013 to April 2014.Forty-seven samples of three brands of peanut were collected in three major markets of the city of Maringa, Parana State, Brazil. The samples were analyzed by thin layer chromatography and confirmed by chemical derivatization with trifluoroacetic acid. Recovery was accomplished by the addition of known quantities of standard solutions satisfactorily test the four aflatoxins (B1 + B2 + G1 + G2) in five samples free of contamination peanuts. Daily likely average intake was assessed by multiplying the average concentration of aflatoxin, found in this study, the average consumption of peanut population of Maringa region (6.7 g / person / day) divided by the average body weight of an adult (70 kg).The average recovery method presented for aflatoxins B1, B2, G1 and G2 106, 120, 106.7 and 90%, respectively. Aflatoxin B1 and B2 were identified in 25.5% of all samples. We did not find any samples with detectable levels of G1 and G2 aflatoxins. All positive samples showed levels above the maximum permitted level for the sum of the four aflatoxins according to Brazilian law. Aflatoxin levels in positive samples ranged from 36-832 μg / kg.The daily average intake probable (IDPM) was 7.4 μg / kg body weight / day for the sum of aflatoxin B1 and B2 aflatoxin. The value found exceeds the maximum daily intake provisional tolerable (IDMTP) of 0.001 μg / kg body weight / day of aflatoxin B1 for adults and children with no diagnosis of hepatitis B and 0.0004 vg / kg body weight / day of aflatoxin B1 to hepatitis virus carriers B. IDPM for aflatoxin B1 (6.5 μg / kg body weight / day) obtained in this study exceeded both IDMTP values, indicating the need for further studies to assess the overall risks for the health of the population by exposure to aflatoxins in Brazil.